International propagation of financial shocks in a search and matching environment - Marlène Isoré (Bank of Finland, 2016)
This paper develops a two-country model in which transmission of financial shocks arises despite a flexible exchange rate regime and substitutable financial assets, contrary to the open-economy literature results under these two conditions. The search and matching approach first accounts for the time needed to restore normal functioning of financial markets following a disruption. It also allows dissociating two types of financial shocks: (i) pure liquidity contractions imply negative co-movements of home and foreign outputs, so that the model nests the standard open macroeconomy results as a particular case; (ii) shocks to banks' capitalization costs in one country do generate international financial contagion.
URN:NBN:fi:bof-201611301504
Keywords: C78; E44; E51; F41; F42; G01; G15; 330